2002
DOI: 10.2105/ajph.92.5.818
|View full text |Cite
|
Sign up to set email alerts
|

HIV and AIDS Risk Behaviors Among Female Jail Detainees: Implications for Public Health Policy

Abstract: Many women at risk for HIV and AIDS--women who use drugs, women who trade sex for money or drugs, homeless women, and women with mental disorders--eventually will cycle through jail. Because most jail detainees return to their communities within days, providing HIV and AIDS education in jail must become a public health priority.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
57
1

Year Published

2005
2005
2017
2017

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 78 publications
(67 citation statements)
references
References 81 publications
9
57
1
Order By: Relevance
“…22 This can be attributed to the high rates of IDU among incarcerated women, which ranges from 14% to 42% nationwide. 23 Also, 80% of study participants were smokers compared with 19.8% in the general population. 24 The high prevalence rates of cervical dysplasia, hepatitis C, and tobacco use in corrections has implications for both primary and secondary prevention as well as treatment of disease.…”
Section: Discussionmentioning
confidence: 92%
“…22 This can be attributed to the high rates of IDU among incarcerated women, which ranges from 14% to 42% nationwide. 23 Also, 80% of study participants were smokers compared with 19.8% in the general population. 24 The high prevalence rates of cervical dysplasia, hepatitis C, and tobacco use in corrections has implications for both primary and secondary prevention as well as treatment of disease.…”
Section: Discussionmentioning
confidence: 92%
“…Our findings also support previous studies which have found high rates of HIV, drug and alcohol use, mental health diagnoses, homelessness and chronic diseases in incarcerated populations. [6][7][8][9][10] While threequarters of participants expressed a desire for drug treatment services, only 13% reported receiving treatment while incarcerated, illustrating a dearth of treatment availability within BCDC. The diagnoses (e.g., depression, bipolar disorder and schizophrenia) named by respondents are consistent with a similar study of female detainees in Chicago.…”
Section: Release From Jail: Moment Of Crisis or Window Of Opportunitymentioning
confidence: 99%
“…1 In addition to differing from incarcerated men, female prisoners also differ from their non-incarcerated counterparts. Compared with adult females in the general population, incarcerated women are more likely to experience substance use, mental illness, intimate partner violence, HIV risk behaviors, 6 HIV, hepatitis B and hepatitis C infection 7 and homelessness. [8][9][10] Furthermore, female detainees who report being homeless upon arrest also report higher numbers of previous arrests, substance abuse, prostitution-related charges, and difficulty accessing drug treatment.…”
Section: Introductionmentioning
confidence: 99%
“…Heteronormative expectations also routinely render queer sexualities invisible in providers' efforts to address the sexual needs of incarcerated women (Zierler & Krieger, 1997). Jail-based programs may represent an opportunity for service providers and advocates to make visible and then address the needs of disenfranchised women (McClelland, Teplin, Abram, & Jacobs, 2002). In contrast to state and federal prisons, jails are city and county facilities in which women usually serve shorter terms, typically 72 hours to 5 months.…”
Section: June 2008mentioning
confidence: 99%